Pesticide residue exposure provides different responses of the microbiomes of distinct cultures of the stored product pest mite Acarus siro - Hubert, Jan; Navratilova, Blanka; Sopko, Bruno; Nesvorná, Marta; Phillips, Thomas W (BMC microbiology, 2022)
BACKGROUND: The contribution of the microbiome to pesticide breakdown in agricultural pests remains unclear. We analyzed the effect of pirimiphos-methyl (PM) on four geographically different cultures of the stored product pest mite Acarus siro (6 L, 6Tu, 6Tk and 6Z) under laboratory experiments. The effect of PM on mite mortality in the impregnated filter paper test was compared. RESULTS: The mite sensitivity to PM decreased in the order of 6 L, 6Tu, 6Tk, and 6Z. Then, the mites were cultured on PM residues (0.0125 and 1.25 μg·g-1), and population growth was compared to the control after 21 days of exposure. The comparison showed two situations: (i) increasing population growth for the most sensitive cultures (6 L and 6Tu), and (ii) no effect on mite population growth for tolerant cultures (6Z and 6Tk). The microbiome of mites was analyzed by quantification of 16S DNA copies based on quantitative polymerase chain reaction (qPCR) and by barcode sequencing of the V4 fragment of 16S DNA on samples of 30 individuals from the control and PM residues. The microbiome comprised primarily Solitalea-like organisms in all cultures, except for 6Z, followed by Bacillus, Staphylococcus, and Lactobacillus. The microbiomes of mite cultures did not change with increasing population density. The microbiome of cultures without any differences in population density showed differences in the microbiome composition. A Sodalis-like symbiont replaced Solitalea in the 1.25 μg·g-1 PM in the 6Tk culture. Sodalis and Bacillus prevailed in the microbiomes of PM-treated mites of 6Z culture, while Solitalea was almost absent. CONCLUSION: The results showed that the microbiome of A. siro differs in composition and in response to PM residues in the diet. The results indicate that Sodalis-like symbionts can help recover mites from pesticide-induced stress.
Keywords: roztoči; mikrobiota; Mites; Animals; Acaridae; Humans; rezidua pesticidů; Microbiota; lidé; Pesticide Residues; zvířata; Bacteroidetes